Enhancing the stability of electrochemical asymmetric supercapacitor by incorporating thiophene-pyrrole copolymer with nickel sulfide/nickel hydroxide composite. (February 2022) - Nath, Anish Reghu; Madhu, Bharath; Mohan, Ajay; N, Sandhyarani
Highlights: Enhanced cyclic stability of a transition metal hydroxide or sulphide is reported. A copolymer of thiophene and pyrrole was incorporated into nickel hydroxide/ nickel sulphide composite. Enhanced the cyclic stability over 94% even after a continuous run of 10, 000 cycles. Asymmetrical supercapacitor showed a power density of 8.65 kW/kg at a current density of 10 A/g. Improvement of stability without altering the morphology and chemical structure of the composite. Abstract: The practical application of a supercapacitor predominantly relies on its sustained cyclic stability. Hence it is essential to develop materials with high stability for the efficient supercapacitor applications. Herein, we demonstrate the integration of a copolymer of poly thiophene-pyrrole (cPPyTh) to surpass the limited cyclic stability of the nickel sulfide/nickel hydroxide (NSH) composite. Though the lower electronegativity of sulfur in coexistence with hydroxide achieves a superior capacity for NSH, it lacks extended cyclic stability. By incorporating cPPyTh into the layers of NSH, the stability of the resultant composite (NCP) could be enhanced by preventing the aggregation of layered NSH during longer runs. NCP electrode provides a specific capacity of 87 C/g at a current density of 1 A/g in a three-electrode system. An energy density of 25.47 Wh/kg and power density of 8.65 kW/kg is obtained for the asymmetric supercapacitor fabricated with NCP as positive and modified activated carbon (MAC) as negative electrode. The NCP demonstrates a superior cyclic stability of over 94% for 10, 000 cycles in comparison to NSH with stability ∼ 73% over 5, 000 cycles for the asymmetric supercapacitor. Graphical abstract: Image, graphical abstract